Septata intestinalis and Encephalitozoon cuniculi: cross-reactivity between two microsporidian species - Schottelius, J; Lo, Y; Schmetz, C (Folia parasitologica, 1995)
An infection with Septata intestinalis was diagnosed in a 35-year-old AIDS patient without diarrhoea. The diagnosis was based on morphological examinations of a duodenal biopsy specimen. Serum antibodies were detected reacting with spores of Encephalitozoon cuniculi. Spores of S. intestinalis and E. cuniculi stained with Brown Hopps Gram stain showed a red colour (Gram negative) and not a blue/black colour which was described for microsporidian spores in tissue.
Keywords: mikrosporidióza; zkřížené reakce; feces; Humans; Duodenum; dospělí; Microsporidiosis; AIDS-Related Opportunistic Infections; Intestinal Diseases, Parasitic; lidé; spory; Cross Reactions; zvířata; Feces; Adult; duodenum; Spores; Male; oportunní infekce doprovázející AIDS; protilátky protozoální; Encephalitozoon cuniculi; Antibodies, Protozoan; Animals; mužské pohlaví; parazitární nemoci střev; Microsporida